PENGARUH SIKLUS HIDUP PERUSAHAAN, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA - AFDINA SASURUW, FIOLINTA (Jurnal Akuntansi AKUNESA, 2019)
ABSTRACTThe purpose of this research is to investigate the effect of firm life cycle, firm size, leverage on earnings management. The samples in this research are 62 Manufacturing Companies of Basic and Chemical Industrial Sectors Listed on Indonesian Stock Exchange Period 2015-2017. This research used multiple liniear regression analysis with SPSS 22 to test the hyphotesis. Based on the results of this study indicate that the companys life cycle variable has a positive effect on earnings management. Then, firm size and leverage variables have no effect on earnings management.Keywords: firm life cycle, firm size, leverage, earnings management